PENGARUH TUJUAN PENYUSUNAN LAPORAN KEUANGAN TERHADAP METODE PENGUKURAN UNTUK UNSUR-UNSUR DALAM LAPORAN KEUANGAN (SEBUAH STUDI ARTIKEL DAN STANDAR AKUNTANSI KEUANGAN INDONESIA) - Etty Gurendrawati (Jurnal Ilmiah Econosains, 2011)
Abstract The financial statements have been prepared by an enterprise through a process of accounting. In the process of recording up to financial reporting, there are stages of recognition, initial measurement, measurement subsequent to initial recognition and presentation. These stages exist in the accounting process as a whole in the preparation of financial statements. Studies conducted on two groups of different views in determining financial reporting purposes. Different financial reporting purpose is the basis of different measurement methods for the same financial statement items. It is also evident from the results of an analysis of the measurement method of accounting in accordance with Financial Accounting Standards applicable in Indonesia. From a study of the Standar Akuntansi Keuangan Indonesia note that measurement inventories use historical cost and net Realization value, for the measurement of fixed assets use historical cost, fair value at the time of revaluation and the recoverable value. As for the obligation to use basic measuring the amount of expenditure required to settle the obligation and alternative estimates using present value of liabilities on the balance sheet date. Still require further study and analysis in order to ensure that the objectives of financial reporting affect the measurement method elements in the financial statements. Keywords: financial reporting purposes, the measurement of the elements of financial statements.